Anthropometric, cognitive, and schooling benefits of measles vaccination: Longitudinal cohort analysis in Ethiopia, India, and Vietnam. Issue 31 (18th July 2019) - Nandi, Arindam; Shet, Anita; Behrman, Jere R.; Black, Maureen M.; Bloom, David E.; Laxminarayan, Ramanan
Abstract: Objective: To estimate the associations between measles vaccination and child anthropometry, cognition, and schooling outcomes in Ethiopia, India, and Vietnam. Methods: Longitudinal survey data from Young Lives were used to compare outcomes at ages 7–8 and 11–12 years between children who reported receipt or non-receipt of measles vaccine at 6–18 months-of-life ( n  = ∼2000/country). Z-scores of height-for-age (HAZ), BMI-for-age (BMIZ), weight-for-age (WAZ), Peabody Picture Vocabulary Test (PPVT), early grade reading assessment (EGRA), language and mathematics tests, and attained schooling grade were examined. Propensity score matching was used to control for systematic differences between measles-vaccinated and measles-unvaccinated children. Findings: Using age- and country-matched measles-unvaccinated children as comparisons, measles-vaccinated children had better anthropometrics, cognition, and schooling. Measles-vaccinated children had 0.1 higher HAZ in India and 0.2 higher BMIZ and WAZ in Vietnam at age 7–8 years, and 0.2 higher BMIZ at age 11–12 years in Vietnam. At ages 7–8 years, they scored 4.5 and 2.9 percentage points (pp) more on PPVT and mathematics, and 2.3 points more on EGRA in Ethiopia, 2.5 points more on EGRA in India, and 2.6 pp, 4 pp, and 2.7 points more respectively on PPVT, mathematics, and EGRA in Vietnam. At ages 11–12 years, they scored 3 pp more on English and PPVT in India, and 1.7 pp more on PPVT in Vietnam. They also attained 0.2–0.3 additional schooling grades across all ages and countries. Conclusion: Our findings suggest that measles vaccination may have benefits on cognitive gains and school-grade attainment that can have broad educational and economic consequences which extend beyond early childhood.